2018
DOI: 10.1097/md.0000000000010732
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of spinal epidural hematoma during vertebroplasty

Abstract: According to our experience, when SCI occurs during vertebroplasty, neurological deficits are always secondary to acute SEH. Timely decompression, particularly transfer surgery, can shorten recovery time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Domenicucci et al 19 reviewed 1,010 SEH cases in 16 years and concluded that 18% of the significant cases were iatrogenic (spinal puncture), while 29% were non-iatrogenic and caused by factors such as clotting, trauma, and pregnancy. However, iatrogenic SEH after PKP or PVP has been reported in seven previous studies [11][12][13][14][15][16][17] (Table 1). Wang et al 11 suspected that SEH after PKP was caused by direct injury from intraoperative puncture.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Domenicucci et al 19 reviewed 1,010 SEH cases in 16 years and concluded that 18% of the significant cases were iatrogenic (spinal puncture), while 29% were non-iatrogenic and caused by factors such as clotting, trauma, and pregnancy. However, iatrogenic SEH after PKP or PVP has been reported in seven previous studies [11][12][13][14][15][16][17] (Table 1). Wang et al 11 suspected that SEH after PKP was caused by direct injury from intraoperative puncture.…”
Section: Discussionmentioning
confidence: 95%
“…This finding was supported by three other studies. [12][13][14] Mattei et al 15 suggested that venous congestion plays a pivotal role in the etiology of SEH. von der Brelie et al 16 attributed the development of SEH after PVP in a patient with long-term oral aspirin to coagulation malfunction owing to aspirin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According Fang et al (2018) 9 a poor prognosis and permanent injury can be associate an inappropriate management of spinal epidural hematoma (SEH), being this pathology an emergent complication. Figure 2 shows an EDH that extends from the level of the second cervical vertebra to the sixth cervical vertebra.…”
Section: Physiopathologymentioning
confidence: 99%
“…Fang et al (2018) 9 suggest that exploratory surgery is a good option in patients who incurs spinal cord injury during vertebroplasty, because neurological deficits occurs secondary to acute spinal epidural hematoma (SEH). Moreover, theses authors affirm that neurological recovery is multifactorial, and the key for the postsurgical success is the timing of surgery, and timely decompression and transfer surgery have a special function to shorten the time of patient recovery.…”
Section: Physiopathologymentioning
confidence: 99%